2023
DOI: 10.1136/bmjresp-2022-001535
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the importance of healthy sleep patterns in the risk of adult asthma under the combined effects of genetic susceptibility: a large-scale prospective cohort study of 455 405 participants

Abstract: BackgroundIndividuals with asthma usually have comorbid sleep disturbances; however, whether sleep quality affects asthma risk is still unclear. We aimed to determine whether poor sleep patterns could increase the risk of asthma and whether healthy sleep patterns could mitigate the adverse effect of genetic susceptibility.MethodsA large-scale prospective study was performed in the UK Biobank cohort involving 455 405 participants aged 38–73 years. Polygenic risk scores (PRSs) and comprehensive sleep scores, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The effects of various factors—physiological changes and physical posture associated with sleep, circadian clock regulation of immune function, and environmental conditions—have yet to be comprehensively teased apart [ 80 ]. Among the few studies assessing the influence of sleep on asthma, a prospective study found that adults with poor sleep habits had a higher risk of asthma within a follow-up period of at least 10 years, while experimental manipulation of sleep duration among asthma patients resulted in a decreased in peak expiratory flow rates and increased interference of activities by asthma symptoms [ 38 , 81 ]. Nonetheless, while the directionality of the relationship between sleep and asthma remains unclear, the association of poor sleep with asthma has been well documented, with short sleep and poor sleep quality being associated with nocturnal respiratory symptoms [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of various factors—physiological changes and physical posture associated with sleep, circadian clock regulation of immune function, and environmental conditions—have yet to be comprehensively teased apart [ 80 ]. Among the few studies assessing the influence of sleep on asthma, a prospective study found that adults with poor sleep habits had a higher risk of asthma within a follow-up period of at least 10 years, while experimental manipulation of sleep duration among asthma patients resulted in a decreased in peak expiratory flow rates and increased interference of activities by asthma symptoms [ 38 , 81 ]. Nonetheless, while the directionality of the relationship between sleep and asthma remains unclear, the association of poor sleep with asthma has been well documented, with short sleep and poor sleep quality being associated with nocturnal respiratory symptoms [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent systematic review found that sleep duration was not significantly associated with AR, while sleep quality score, sleep disturbance scores, and sleep latency scores were higher among AR patients; sleep efficiency was nonetheless decreased among AR patients [ 37 ]. Finally, poor sleep patterns have been found to increase asthma risk [ 38 ]. While asthma has been associated with poor sleep quality, this was likely the result of asthma symptoms affecting sleep, or comorbid AR resulting in AR-related sleep disturbances in asthmatics [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy sleep lowered the risk of asthma in all genetic susceptibility groups, HR being 0.63 (0.57–0.70) in the high-risk group. Risk analysis suggests that 19% of asthma cases could be prevented by improved sleep traits ( 75 ).…”
Section: Other Risk Factors For Late Onset T2 Eosinophilic Asthmamentioning
confidence: 99%
“…Apart from sinonasal symptoms, CRSwNP is associated with an increased risk of asthma, otitis media, depression and social dysfunction (6). Similarly important is the extensively studied association between CRSwNP and sleep disturbance, which is linked to cardiovascular and cerebrovascular disease and reduced quality of life for both the patient and their partner (7)(8)(9). The impact of CRSwNP on quality of life (QoL) has been observed to be equivalent to other chronic conditions such as chronic obstructive pulmonary disease (COPD), congestive heart failure, and diabetes (10,11).…”
Section: Introductionmentioning
confidence: 99%